Business Competitiveness: Building and Applying the 3Cs and the Strategic Change Matrix Across COVID-19 (Global Journal of Science Frontier Research, 2020)
This India-wide, empirical, point-in-time, global literature-supported, quantitative study involves 232 leading management consulting firm (MCF) consultants and contracting client firm (CF) perspectives. It relationally builds a structural MCF-CF 3Cs model that links MCF competencies into MCF-CF capabilities systems and then into CF business competitiveness. The 3Cs model can be visually and numerically presented as a CF three-dimensional positioning within the strategic change matrix. Future pathways towards a new optimal strategic future CF position can then be strategic change matrix mapped. A contribution towards Management-Consulting-Theory is presented as one that likely follows and embodies the MCF-CF 3Cs model processes.
Keywords: business competitiveness; strategic change matrix; 3cs model; sustainable performance